Formative assessment in the learning and teaching of design and technology - Black, Paul (Design and Technology Education: An International Journal, 2008)
The first parts of this paper summarise recent work on the development of formative assessment methods, set out a precise definition of formative assessment, and discuss briefly the aims of Design and Technology which such methods should help to achieve. The following sections discuss in turn feedback in questioning and classroom dialogue, feedback given in writing, peer- and selfassessment and its link to development of peer-group work amongst students, and the formative use of assessment designed primarily to serve summative purposes. These sections include examples of classroom work in design and technology, drawn mainly from other authors. In a closing section I argue that any successful development of formative assessment will depend on implementation of two key strategies. One must aim for careful selection and presentation of tasks which both reflect the key aims of the subject and provide opportunities to engage students in formative dialogue. The other is to create opportunities, including allotted time, for collegial sharing between the various teachers of these students in order to secure both consistency for those students and mutual support between teachers in developments which have been found to be both challenging yet rewarding.